Adolescents’ academic achievement and life satisfaction: the role of parents’ education - Crede, Julia; Wirthwein, Linda; McElvany, Nele; Steinmayr, Ricarda (Frontiers in Psychology, 2015)
Drawing on the background of positive psychology, there has only recently been a focus on adolescents’ life satisfaction in the context of education. Studies examining the relationship between adolescents’ academic achievement and life satisfaction have shown conflicting results and the reasons are not fully understood. The present study investigated the role of parents’ education as a potential moderator of the relationship between adolescents’ academic achievement and life satisfaction. A sample of German high school students (N=411) reported parents’ educational attainment, as an indicator of family socio-economic status (SES), and students’ academic achievement was operationalized by grade point average (GPA) in five subjects. Results indicated that only mothers’ education functioned as a moderator of the relationship between academic achievement and students’ life satisfaction. The association between academic achievement and life satisfaction was only found in the group of students whose mothers had achieved the same or a higher education (at least high school diploma) as their own children. Fathers’ educational attainment, however, was not a significant moderator of the respective relationship. Directions for future research and the differential influences of fathers’ and mothers’ education are discussed with regard to potential underlying processes.